Hubungan Antara Kesepian dengan Online Self-Disclosure pada Remaja yang Menggunakan Instagram di Bukittinggi - Ulfah, Novia Marida; Aviani, Yolivia Irna (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Loneliness is a subjective feeling that arises through emotional reactions and is the result of an individual's perception of interpersonal relationships and satisfaction with social relationships. Online self-disclosure exists as a form of coping with the loneliness felt by teenagers. Instagram is a social media for online self-disclosure. This research aims to obtain empirical data and to determine the relationship between loneliness and online self-disclosure among teenagers who use Instagram in Bukittinggi. This research uses a correlational quantitative approach. The subjects of this study amounted to 297 teenage Instagram users in Bukittinggi using cluster random sampling techniques. Data is processed using product moment correlation with SPSS 25 for windows. The results of the analysis showed that there was a significant relationship between loneliness and online self-disclosure in adolescents who used Instagram in Bukittinggi.